Blood cell characterization and transcriptome analysis reveal distinct immune response and host resistance of different ploidy cyprinid fish following Aeromonas hydrophila infection. Issue 120 (January 2022) - Xiong, Ning-Xia; Ou, Jie; Fan, Lan-Fen; Kuang, Xu-Ying; Fang, Zi-Xuan; Luo, Sheng-Wei; Mao, Zhuang-Wen; Liu, Shao-Jun; Wang, Shi; Wen, Ming; Luo, Kai-Kun; Hu, Fang-Zhou; et al.
Abstract: Aeromonas hydrophila can pose a great threat to survival of freshwater fish. In this study, A. hydrophila infection could decrease blood cell numbers, promote blood cell damage as well as alter the levels of alkaline phosphatase (ALP), lysozyme (LZM), aspartate aminotransferase (AST), total antioxidant capacity (T-AOC), total superoxide dismutase (SOD), catalase (CAT) and malondialdehyde (MDA) in immune-related tissues of red crucian carp (RCC, 2 N = 100) and triploid cyprinid fish (3 N fish, 3 N = 150). In addition, the significant alternation of antioxidant status was observed in PBMCs isolated from RCC and 3 N following LPS stimulation. The core differential expression genes (DEGs) involved in apoptosis, immunity, inflammation and cellular signals were co-expressed differentially in RCC and 3 N following A. hydrophila challenge. NOD-like receptor (NLR) signals appeared to play a critical role in A. hydrophila- infected fish. DEGs of NLR signals in RCCah vs RCCctl were enriched in caspase-1-dependent Interleukin-1β (IL-1β) secretion, interferon (IFN) signals as well as cytokine activation, while DEGs of NLR signals in 3Nah vs 3Nctl were enriched in caspase-1-dependent IL-1β secretion and antibacterial autophagy. These results highlighted the differential signal regulation of different ploidy cyprinid fish to cope with bacterial infection. Highlights: Blood cells of triploid cyprinid fish exhibited a higher resistance against A. hydrophila -induced cell damage. Acute A. hydrophila infection could dramatically alter non-specific immunity in different ploidy cyprinid fish. Acute A. hydrophila infection could trigger the difference in signal regulation in different ploidy cyprinid fish.